Efficient on-the-fly category retrieval using ConvNets and GPUs - Chatfield, K; Simonyan, K; Zisserman, A (Springer Nature, 2015)
We investigate the gains in precision and speed, that can be obtained by using Convolutional Networks (ConvNets) for on-the-fly retrieval – where classifiers are learnt at run time for a textual query from downloaded images, and used to rank large image or video datasets.